Evolution of Cryoglobulinemia in Direct-Acting Antiviral-Treated Asian Hepatitis C Patients With Sustained Virological Responses: A 4-Year Prospective Cohort Study - Chang, Ming-Ling; Cheng, Jur-Shan; Chuang, Ya-Hui; Pao, Li-Heng; Wu, Ting-Shu; Chen, Shiang-Chi; Chang, Ming-Yu; Chien, Rong-Nan (Frontiers in Immunology, 2022)
Background How cryoglobulinemia evolves after sustained virological response (SVR) following direct-acting antiviral (DAA) treatment in Asian hepatitis C virus (HCV)-infected patients remains elusive. Methods A prospective cohort study was conducted in 422 Taiwanese patients (358 completed DAA therapy and 353 experienced SVRs). Serum cryoglobulins were surveyed at baseline and every 3-6 months posttherapy. Results Of 422, 227 (53.8%) had cryoglobulinemia, 8 (1.89%) had cryoglobulinemic vasculitis. Of 227, 54 (23.8%), 57 (25.1%) and 116 (51.1%) had 1, 2 and 3 cryoglobulins, respectively; those with 3 cryoglobulins had the highest alanine aminotransferase, immunoglobulin G (IgG) and fibrosis-4 index. During a 4-year follow-up, among SVR patients, cryoglobulinemia rates decreased from 56.4% to 15.4%, single cryoglobulin rates increased (21.6% to 63.9%) and 3 cryoglobulin rates decreased (55.7% to 11.1%). Compared with baseline values, among SVR patients with baseline cryoglobulinemia, complement component 4 levels increased, and IgG and IgM levels decreased until 48 weeks posttherapy for those without posttherapy cryoglobulinemia. All cryoglobulinemic vasculitis patients exhibited SVRs; 5 (62.5%) achieved complete clinical response 12 weeks posttherapy, of whom, 2 (40%) experienced clinical relapse 24~48 weeks posttherapy. Baseline IgM levels were associated with posttherapy cryoglobulinemia in SVR patients (cut-off values at 12, 24, 48 weeks and 4 years posttherapy: 130, 105, 118 and 168 mg/dL, respectively). Conclusions Among DAA-treated SVR patients, in 4 years, cryoglobulinemia rates decreased from 56.4% to 15.4%, multiple cryoglobulin rates decreased, cryoglobulinemia signals reversed, 62.5% of cryoglobulinemic vasculitis patients achieved complete clinical response (40% had relapse), and baseline IgM levels indicated posttherapy cryoglobulinemia.